Stochastic algorithms for white matter fiber tracking and the inference of brain connectivity from MR diffusion tensor data - Sergej M. Prigarin; Klaus R. Hahn (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2004)
We consider several stochastic algorithms for fiber tracking and compute the connectivity matrix from data obtained by magnetic resonance diffusion tensor imaging of the living human brain.
urn:nbn:de:bvb:19-epub-1777-9
Keywords: 519; diffusion tensor imaging (DTI); stochastic fiber tracking; brain connectivity